Value Creation with Big Data in Marketing: An Empirical Evidence on SMEs - Sampurno Wibowo; Yuyus Suryana; Umi Kaltum (Asian Journal of Business and Accounting, 2021)
ABSTRACT Manuscript type: Research paper Research aims: This study investigates the impact of big data marketing on the ability of SMEs to create value through the relationship quality. Design/Methodology/Approach: Data were collected from 150 SMEs in West Java. Structural Equation Modelling (SEM) was employed to test the research model. Research findings: The results of the study indicated that big data use for marketing purposes had a positive impact on value creation and relationship quality. Surprisingly, this study demonstrated insubstantial evidence to associate relationship quality with value creation. The effect of relationship quality as a mediator between big data use and value creation was also not significant. Theoretical contribution/Originality: This study extends on existing literature by providing empirical evidence showing the importance of big data in stimulating value creation and relationship quality in the Indonesian culinary industry. Practitioner/Policy implication: The outcome of this research suggests SMEs to quickly adapt to the dynamic business environment by investing in big data, as it has the potential for high business value. The use of big data can also facilitate SMEs to better manage their relationships with customers. The ability of small businesses to use data is a crucial factor in creating new development for business continuity, accompanied by establishing relationships based on data. Research limitation/Implications: To increase the generalisability of this study, future research needs to consider collecting data from different types of populations and countries. Keywords: Big Data Marketing, Relationship Quality, Value Creation, SME, Culinary JEL Classification: M12